1992
DOI: 10.1136/thx.47.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Use of induced sputum cell counts to investigate airway inflammation in asthma.

Abstract: Background Airway inflammation is considered to be important in asthma but is relatively inaccessible to study. Less Airway inflammation is a major factor in the pathogenesis of asthma. Mast cell and eosinophil infiltration, epithelial damage, and mucus production are characteristic features.' Direct examination of the inflammatory response should help to improve understanding of the pathogenesis and treatment of asthma.In patients with stable asthma bronchial biopsy and bronchoalveolar lavage have been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
670
1
26

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 851 publications
(716 citation statements)
references
References 20 publications
(6 reference statements)
19
670
1
26
Order By: Relevance
“…The original studies introducing the sputum induction method reported few side-effects and no fall in FEV1 [15,16]. Studies concentrating upon safety aspects of sputum induction have found it safe even in patients with severe asthma [6±9] and in COPD [1±4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original studies introducing the sputum induction method reported few side-effects and no fall in FEV1 [15,16]. Studies concentrating upon safety aspects of sputum induction have found it safe even in patients with severe asthma [6±9] and in COPD [1±4].…”
Section: Discussionmentioning
confidence: 99%
“…min -1 , particle-size 4.5 mm). The original paper on asthmatics by PIN et al [15] used a relatively low-output ultrasonic nebulizer (output 0.9 mL . min -1 , particle-size 5.6 mm), with which significant bronchoconstriction rarely occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Eur Respir J 2000; 16: 324±329. The method of induced sputum is widely used as a noninvasive procedure for obtaining biological samples from the airways [1,2] in order to determine their cellular and biochemical composition in relation to airway diseases [3,4]. As sputum cells are embedded in airway secretions, the material has to be liquified in order to prepare singlecell suspensions for flow cytometry.…”
mentioning
confidence: 99%
“…Basically two protocols describing the procedure of induction and subsequent processing of samples have been proposed [1,2]. These protocols have been modified in multiple respects subsequently, and the procedures used by different research groups vary considerably in detail.…”
Section: Induction and Processingmentioning
confidence: 99%